Document review of the paper-based implementation of the Framework and strategy for disability and rehabilitation in Gauteng, South Africa - Naeema Ahmad Ramadan Hussein El Kout; Natalie Benjamin-Damons; Sonti Imogene Pilusa (PLoS ONE, 2025)
Background The prevalence of disability is on the rise globally and in South Africa, with a high number of unmet needs and poor actualisation of the health rights of persons with disabilities. A tool to realise these rights is health policy, such as the framework and strategy for disability and rehabilitation (2015-2022)(FSDR). There are limited data on the implementation outcomes of the FSDR. Objective To review the implementation of the FSDR according to the paper-based provincial reports. Methods The study conducted a document review and utilised a concurrent mixed-method design, combining qualitative and quantitative data extracted from paper-based evaluation templates developed by the South African National Department of Health (NDoH). The qualitative analysis involved thematic coding using the RE-AIM framework to examine the FSDR’s implementation across eight provinces, while quantitative data, such as frequencies and percentages, provided supplementary insights. Results The quantitative results revealed that 87% of the reports from provinces reported physical accessibility to the FSDR, and 62% of provinces received training on the implementation of the FSDR. Only two out of eight provinces have conducted monitoring and evaluation since implementing the FSDR in 2015. Qualitative findings revealed poor reach and adoption of the FSDR owing to a lack of implementation training for end users. The lack of indicators resulted in poor maintenance of the FSDR, as well as the lack of human resources and equipment which resulted in the reduced efficacy of the FSDR. Conclusion The FSDR has not achieved its full level of implementation due to numerous barriers, such as lack of resources, human capacity, and training on implementation.